Wikipedia in Education: Acculturation and learning in virtual communities. (December 2015) - Brailas, Alexios; Koskinas, Konstantinos; Dafermos, Manolis; Alexias, Giorgos
Abstract: The present study investigates on the learning impact of utilizing Wikipedia's community in education. Today, many instructors assign their students editing Wikipedia's articles as part of their coursework. Participation in a cyber-community during an educational assignment exposes students to a brand new culture and netiquette, to a set of explicit and tacit rules and cultural norms. This requires students to internalize the embedded online culture in order to join the community — a form of acculturation which may cause stress, but which can lead to opportunities for growth, learning and development. By taking advantage of a virtual community, educators can literally bring a whole thriving community into their classrooms. The acculturation of the educational group into the culture of a hosting virtual community, through collaborative actions, conflicts and disturbances, results to the formation of a collective zone of proximal development: what the students' group manages to perform today with the aid of the community's members will be performed independently tomorrow. The formation of a virtual learning community through the procedural and structural coupling of two discrete activity systems opens a new space for participatory learning.